Forming professional thinking among future medical pedagogists - G.N, Kurbanova (Middle European Scientific Bulletin, 2021)
The given article analyzes the ways of forming professional thinking future teachers of medical educational institutions. The article describes the content of the organization of lectures aimed at activating the learning activities of students in higher education institutions and the use of modern methods to ensure its effectiveness. There are also comments on important factors in the development of professional thinking